EVALUASI PELAKSANAAN RENCANA KERJA (RENJA) KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU TAHUN 2015 - Arindi, Mutia; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Payung Sekaki district Action Plan (Renja) is a planning document for a one-year period. Law No. 17 of 2007 on the national development planning system and Law No.2 of 2015 on local government has required each unit of regional apparatus to prepare work plans as work guidelines for a period of one year and serves to translate five strategic plans annual basis as outlined in the Renstra into annual planning that is more operational. Problems in the implementation of Payung Sekaki district Action Plan is the lack of quality of staff in running the program, fund changes, apparatus resources and facilities at Payung Sekaki district and time constraints. Research objectives: 1) To know the evaluation of the implementation of work plan Payung Sekaki District Year 2015, 2) To determine what factors affect the implementation of the work plan Payung Sekaki district.The concept of theory that uses Mulyono and Yumari (2017) as guidelines for evaluation research implementation 1) Input is what will be used 2) Output is what is produced, 3) Outcome is what will be achieved. The informant of this research is taken from Secretary of Sub-district and Sub section of Payung Sekaki Sub-district. Population used as informant because this research use qualitative research. Types and data sources use primary data, ie data obtained directly from respondents and secondary data, ie data obtained through reports, books and documents. Techniques of collecting data using interviews, observation and documentation.Data analysis techniques by means of data collection, data reduction, data presentation, and draw conclusions.From the results obtained in the research implementation of Payung Sekaki district Action Plan how much the target of the implementation of the work plan can be clearly illustrated that the implementation of this renja is still experiencing many obstacles or obstacles and not all of them run smoothly. In Payung Sekaki district impact on the development process. Factors affecting the inhibition of the implementation of Payung Sekaki district Project work plan in 2015 are Funds and Budget, Time and Resources.Thus it is concluded that the evaluation of the implementation at Payung Sekaki district is unoptimal in the quality of the implementation because the evaluation aims to determine the quality of an executed implementation.Keywords: Evaluation, Work Plan, Program, Payung Sekaki district